Tourists Intention to Choose Halal Restaurants in Malaysia: A Conceptual Paper - Mohamed, Muharis; Patwary, Ataul Karim; Abumandil, Mohanad S.S. (South Asian Journal of Social Sciences and Humanities, 2021)
Muslims around the world are concerned about the halal concept. Consumers are becoming  more aware of health, making halal food interest in today's business. Today has huge  potential in capturing non-Muslim as the target market. Halal food has gone far beyond the  values of only about religion. The restaurant industry must explore the concept of halal in  more detail. In the restaurant industry, halal represents hygiene, cleanliness and the quality of  the food consumed. This study examines the influence of the halal concept on customers'  intention in choosing a restaurant as their preferred eating place. By using the intercept  survey method, data were collected in Klang Valley, Malaysia. The present study confirms  previous findings on the relationship between attitudes towards halal intention. Customers  with high halal attitudes concern are more willing to purchase from halal-certified  restaurants. The present study also found a positive and significant relationship between halal  awareness and intention to choose Halal restaurants among tourists.
Keywords: Tourists Intention; Halal Restaurant; Malaysia